Inclusion as Domination of Other by Himself/Herself - Alfredo Veiga-Neto; Maura Corcini Lopes (Universidad Pedagógica Nacional, 2013)
From the comprehension of the concepts of: biopolitics, governmental, and paranormal/abnormal, in the way they were developed by Michel Foucault, this article analyses the current policies and practices of social inclusion, as devices implied in an operation of folding of other by himself/herself. Exploring the polysemy of the pair inclusion / exclusion, it is argued that the imperative of inclusion is installed according to bio-politics and at the service of neoliberalism.